Fibrinogen and rhegmatogenous retinal detachment: a pilot prospective study - IP Theocharis (Dove Medical Press, 2010)
IP TheocharisOphthalmology Department, Iaso General Hospital, Athens, GreecePurpose: To examine the correlation, if any, between fibrinogen plasma levels (FPL) and the clinical features of rhegmatogenous retinal detachment (RRD).Methods: FPL were measured preoperatively in 33 patients with primary RRD. Patient characteristics and detachment features such as the numbers of breaks and the extent of the detachment were recorded;Results: No statistically significant correlation was found between FPL and the number of breaks. A statistically significant correlation was found between FPL and the extent of the RRD, even if the influence of the number of breaks was excluded. Conclusions: FPL correlate with retinal detachment extent, which implicates an acute inflammatory response to detachment traumatic phenomenon or a role of the fibrinogen molecule in retinal adhesiveness.Keywords: fibrinogen, retinal detachment, pathogenesis